Public health leadership in India: Reflections from my journey - Anand Krishnan (Wolters Kluwer Medknow Publications, 2018)
Public Health discipline has evolved and currently focuses on addressing social determinants of health and working multi-sectorally to promote health. Public Health Leadershipis the practice of mobilizing people, organizations, and communities to effectively tackle tough public health challenges. Leadership is a core competency of public health.Leaders are people with Vision, Influence, Values and Passion to achieve personal and organizational mission.Leadership is not a personal trait but is learnable skill. Leadership is a journey where one goes from being a member of a single team to lead health sector in working with other sectors. A leader moves from carrying out assigned tasks at the beginning of journey to providing a vision to motivate others to achieve their life goals. A true leader grooms leaders to establish a legacy of leadership. Ten lessons from my life would be: Believe in yourself; Seize the opportunities; present a vision of future; get out of comfort zone; expand capacity rather than define limits; strengthen communication and people to people skills; build a team; consider everyone as a potential collaborator; focus on deliverables and on relationships. We should start Public Health leadership course and develop core modules for teaching of leadership to post graduates in all medical schools.